2023
DOI: 10.3390/nu15112469
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Coffee and Tea Consumption at Midlife and Risk of Dementia Later in Life: The HUNT Study

Abstract: Background: Studies exploring the possible protective effect of coffee and tea consumption on dementia have shown inconsistent results so far. We aimed to investigate whether consumption of tea and different types of coffee at midlife are associated with dementia later in life and whether sex or ApoE4 influence such association. Methods: We included 7381 participants from the Norwegian HUNT Study. Self-reported questionnaires assessed daily consumption of coffee and tea at baseline. After 22 years, individuals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The intake of coffee/tea proved beneficial for cognition, directly impacting cognitive outcomes, consistent with other reports [ 20 , 29 , 30 ]. We believe that caffeine intake from coffee and tea affects MMSE cognitive performance, although there are conflicting findings in the literature [ 31 , 32 , 33 ]. This study discovered a correlation between the frequency of food consumption and cognitive function but did not account for intake dosage and adherence duration.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of coffee/tea proved beneficial for cognition, directly impacting cognitive outcomes, consistent with other reports [ 20 , 29 , 30 ]. We believe that caffeine intake from coffee and tea affects MMSE cognitive performance, although there are conflicting findings in the literature [ 31 , 32 , 33 ]. This study discovered a correlation between the frequency of food consumption and cognitive function but did not account for intake dosage and adherence duration.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies have found a protective effect of coffee on cognitive health. A recent study published in 2023 found no association between coffee consumption and cognitive decline [ 25 ].…”
Section: Discussionmentioning
confidence: 99%